Presencia de cromogranina a en el duodeno fetal y adulto de Myocastor coypus bonariensis (coipo) - Eyheramendy, V. (2016)
The aim of the present study was to identify the presence of hormonal secretory cells and localize them in the fetal and adult duodena of the coypu (Myocastor coypus bonariensis), using a polyclonal antibody developed for detection of chromogranin A. Duodena from fetus aging 60, 75, 90, 105, 120 and 135 days post-coitum (dpc), and from adults were used. Samples were fixed and then embedded in paraffin until analysis. Serial cuts of 5 mm were obtained and were processed with routine histological techniques. An immunohistochemical technique (avidin-biotin-peroxidase) was used to detect the hormonal secretory cells. In adults, chromogranin A was identified in cells next to the enterocytes of the surface epithelium of the intestinal villi and in the luminal epithelium of Lieberkhün crypts. In fetal duodenum of 90 dpc, positive cells were detected between the epithelial cells, while in the duodenum of fetus of 120 and 135 dpc, the positive cells were distributed heterogeneously and\nshowing morphological diversity.